Pengaruh Pelatihan Kewirausahaan Dan Komitmen Kerja Terhadap Motivasi Wirausaha - Dewi Sri; MFS Sulistyawati; Feby Astrid Kesaulya (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The objective of this research was to find out the impact of entrepreneurship training and working commitment to entrepreneurship motivation. The type of this research was quantitative research and causal associative. The population of this research was all participants of entrepreneurship training for 3 (years), meanwhile the sample was taken by using purposive sampling method to the participants who were having 80% attendance. Data analysis techniques which were used in this study were classic assumption test and multiple regression test. Sample of this research were 34 respondents in total from SMEs who were the participants of entrepreneurship training in Musi Charitas Catholic University community service. The result of the test showed that entrepreneurship training affected the entrepreneurship motivation, as well as working commitment.